Application Of Cognitive Behavioral Therapy (CBT) In An Effort To Prevent Postpartum Depression - Illustri , Illustri (Sean Institute, 2024)
In some countries, the prevalence of postpartum depression is relatively higher. Postpartum depression can have a negative impact on the mother's physical and mental health, and can affect the relationship between mother and baby. Cognitive behavioral therapy (CBT) is an approach that focuses on changing behavior and ways of thinking, as well as increasing the mother's ability to deal with stress and pressure. Therefore, to study this problem, researchers are interested in conducting research on the application of cognitive behavioral therapy (CBT) in an effort to prevent postpartum depression in the working area of the Makrayu health center in Palembang city. The design of this study was quasi experiment, the sample was normal postpartum mothers day 10-40. The number of samples was 15 experimental groups and 15 control groups with purposive consequtive sampling technique. To measure postpartum depression using EPDS (Edinburg Postnatal Depression Scale). From the results of the study it can be concluded that the results of the unpaired t-test obtained a significance value of 0.003, this means